2020
DOI: 10.1073/pnas.1919176117
|View full text |Cite
|
Sign up to set email alerts
|

Viral zoonotic risk is homogenous among taxonomic orders of mammalian and avian reservoir hosts

Abstract: The notion that certain animal groups disproportionately maintain and transmit viruses to humans due to broad-scale differences in ecology, life history, and physiology currently influences global health surveillance and research in disease ecology, virology, and immunology. To directly test whether such "special reservoirs" of zoonoses exist, we used literature searches to construct the largest existing dataset of virus-reservoir relationships, consisting of the avian and mammalian reservoir hosts of 415 RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
302
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(337 citation statements)
references
References 54 publications
8
302
0
6
Order By: Relevance
“…Closing 50 markets appears frivolous at best ( 23 ); (iii) The focus on so-called high-risk species lacks evidence and defies enforcement. Numerically abundant orders such as rodents and bats harbor more viruses, but the notion of “special viral reservoirs” has recently been revoked ( 24 ). Most pathogens in wildlife remain unidentified, and many spillover events are overlooked ( 19 ).…”
Section: What Needs To Be Done Now?mentioning
confidence: 99%
“…Closing 50 markets appears frivolous at best ( 23 ); (iii) The focus on so-called high-risk species lacks evidence and defies enforcement. Numerically abundant orders such as rodents and bats harbor more viruses, but the notion of “special viral reservoirs” has recently been revoked ( 24 ). Most pathogens in wildlife remain unidentified, and many spillover events are overlooked ( 19 ).…”
Section: What Needs To Be Done Now?mentioning
confidence: 99%
“…This fact has warranted various analyses into the factors that shape the zoonotic potential of viruses and their patterns of cross‐species transmission. For example, RNA viruses and those transmitted by arthropod vectors are more likely to infect humans (Olival et al., 2017), and host taxa such as rodents and bats generally harbour more zoonotic viruses by nature of being more speciose than other orders of mammals or birds (Mollentze & Streicker, 2020). Cross‐species transmission of viruses is further structured by seemingly general phylogeographic rules, such that more phylogenetically similar host species and those with greater geographic overlap are more likely to share viruses (Albery, Eskew, Ross, & Olival, 2020).…”
Section: Figurementioning
confidence: 99%
“…The complex issue of whether bats have evolved to be especially convivial viral reservoirs has drawn attention and has been reviewed well elsewhere ( 3 , 7 9 ). Some analyses ( 2 , 10 ) but not others ( 11 ) have suggested that, per species, bats host more zoonotic viruses than rodents and other mammalian orders. Bat characteristics that could contribute to disproportionate viral reservoir capacity include abundance; aggregation in large, dense colonies; ability to propagate viruses widely as the only mammals that have achieved flight; extreme longevity relative to size and metabolic rate (many species live longer than 25 years) ( 7 ); and distinctive innate immune system properties ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%